The Implementation of Pyrolisis of Waste Material to Bio-Oil in The KKN Course - Lutfia Isna Ardhayanti; Mai Anugrahwati; Rico Nurillahi; Ahmad Saeful; Khuswatun Khasanah; Wati Retno Diah (Universitas Islam Indonesia, 2018)
Kuliah Kerja Nyata (KKN) is one kind of university contribution to community. Through KKN, student also learn how to apply their knowledge and contribute it to community need. In Universitas Islam Indonesia (UII) there are two kind of KKN which are Reguler and Pembelajaran Pemberdayaan Masyarakat (PPM), which differentiate from the topic used. KKN PPM already has major topic that obtained from village destination need. The problem from KKN PPM is limitation time for student to learn about major topic before socialize to community like in KKN UII 57 unit 310-315 which has pyrolisis method as their major topic. Not all the sudent that include in unit 310-315, which come from different study, understand about pyrolisis. To settle this problem, experimental method was choose as learning method used, which help student understand about pyrolisis in limitation time. The effectiveness of this method was observed by observation, interview and questioner. The result show that expertimental method give good result. The student understand basic concept of pyrolisis process that needed in limitation time, eventhough they did not understand anything about pyrolisis method before.